Pengembangan Desain Pembelajaran dan Implementasinya: Antara Idealita dan Realita pada Guru PAI SMP di Kabupaten Semarang - Ayu Rizkia Silviana; Asri Nurdiana; Rahmat Hariyadi (CV Edujavare Publishing, 2025)
This study aims to analyze the implementation of learning design applied by Islamic Religious Education (PAI) teachers at the Junior High School (SMP) level. The focus of this study is to determine (1) How is the process of preparing learning design by PAI teachers in Semarang Regency, (2) How is the implementation of learning design in the learning process in the classroom, (3) Is there a gap between the design and implementation of learning, (4) the factors causing the gap, and (5) the impacts arising from the gap on the quality of PAI learning. The research method uses a mix of methods through qualitative and survey instruments. Data were collected by distributing closed questionnaires to 34 PAI teachers in several randomly selected areas. The results of the data analysis showed that the implementation of learning design by PAI teachers was in the